TINJAUAN YURIDIS PERLINDUNGAN HUKUM TERHADAP TENAGA KERJA INDONESIA DI MALAYSIA - Rasyid, Wahyu; Abejo, Dodie Baltazar Taher; Sunita, Sunita (Program Studi Ilmu Hukum Universtitas Muhammadiyah Gorontalo, 2025)
Indonesia is one of the largest countries that sends its citizens to work abroad. However, many of them experience injustice in their rights and experience inappropriate treatment. This research has two problem formulations, namely how to review the juridical protection of Indonesian workers in Malaysia based on the law. No. 18 of 2017 concerning the protection of Indonesian migrant workers, and how BP2MI is trying to reduce the illegal sending of Indonesian workers based on Law Number 18 of 2017 concerning the protection of Indonesian migrant workers. The purpose of this research is to find out how the juridical review of legal protection for Indonesian workers in Malaysia is based on the law. No. 18 of 2017 concerning the protection of Indonesian migrant workers, and to find out how BP2MI is trying to reduce the illegal sending of Indonesian workers based on Law Number 18 of 2017 concerning the protection of Indonesian migrant workers. This research uses a type of empirical normative research. The data collection techniques used were literature study, field study and interviews. From the results of this research, it can be concluded that the role of the Indonesian migrant worker protection agency (BP2MI) is in seeking protection for Indonesian migrant workers.